Analisis Kesesuaian Postur Kerja Pada Pekerja Bengkel - Nazua Nabila; Firstika Nabilla Balqis; Muthia Afrah Goslan Siregar; Muhammad Amru Siddiq; Triski Alfino; Nanda Mardyanti Br.Purba; Mila Zahara; Zuhrina Aidha (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
This case study research was conducted at a motorbike repair shop located on Lap Road. Golf, Kp. Tengah, Kec. Pancur Batu, Deli Serdang Regency, North Sumatra 20353. This workshop has several workers whose posture is less ergonomic when working. This research aims to find meaning, investigate processes, and gain in-depth understanding and understanding starting from certain individuals, groups or situations. This research uses a qualitative approach to obtain primary data by conducting direct interviews with business actors. This research involves several important processes such as asking questions and procedures, as well as analyzing data inductively. The research results show that the results of the work posture assessment using RULA and REBA data processing with a final score result is 7 which means high risk. In connection with these results, it is necessary to investigate and change the work posture by providing a work desk to make it more ergonomic.